Feminist metaphysics and philosophical methodology - Mikkola, M (Wiley, 2016)
Over the past few decades, feminist philosophy has become recognised as a philosophical sub-discipline in its own right. Among the ‘core’ areas of philosophy, metaphysics has nonetheless until relatively recently remained largely dismissive of it. Metaphysics typically investigates the basic structure of reality and its nature. It examines reality’s putative building blocks and inherent structure supposedly ‘out there’ with the view to uncovering and elucidating that structure. For this task, feminist insights appear simply irrelevant. Moreover, the value-neutrality of metaphysics seems prima facie incompatible with feminism’s explicitly normative stance in that feminist philosophy involves advocacy: speaking on behalf of some group on political grounds. The prospects of feminist metaphysics thus look grim. Nonetheless, feminist philosophers have in recent years increasingly taken up explicitly metaphysical investigations. The basic ideas behind such investigations can be summed up as follows: feminist metaphysics is about negotiating the natural and going beyond the fundamental. In so doing, feminist investigations have expanded the scope of metaphysics. Further, feminist philosophers typically bring new methodological insights to bear on traditional ways of doing philosophy.With this in mind, the article considers the following questions: when thinking about philosophical methodology, how does feminist metaphysics fare relative to ‘mainstream’ metaphysics? More specifically, is feminism’s political advocacy inconsistent with apparent objectivity that some prominent contemporary versions of metaphysics are committed to?